CD44 and CXCL9 serum protein levels predict the risk of clinically significant allograft rejection after liver transplantation. Issue 9 (21st July 2015) - Raschzok, Nathanael; Reutzel‐Selke, Anja; Schmuck, Rosa Bianca; Morgul, Mehmet Haluk; Gauger, Ulrich; Prabowo, Kukuh Aji; Tannus, Laura‐Marie; Leder, Annekatrin; Struecker, Benjamin; Boas‐Knoop, Sabine; Bartels, Michael; Jonas, Sven; et al.
<x xml:space="preserve">Abstract</x> The diagnosis of acute cellular rejection (ACR) after liver transplantation is based on histological analysis of biopsies because noninvasive biomarkers for allograft rejection are not yet established for clinical routines. CD31, CD44, and chemokine (C‐X‐C motif) ligand (CXCL) 9 have previously been described as biomarkers for cross‐organ allograft rejection. Here, we assessed the predictive and diagnostic value of these proteins as serum biomarkers for clinically significant ACR in the first 6 months after liver transplantation in a prospective study. The protein levels were measured in 94 patients immediately before transplantation, at postoperative days (PODs) 1, 3, 7, and 14 and when biopsies were performed during episodes of biochemical graft dysfunction. The CD44 serum protein levels were significantly lower at POD 1 in patients who experienced histologically proven ACR in the follow‐up compared with patients without ACR (P < 0.001). CXCL9 was significantly higher before transplantation (P = 0.049) and at POD 1 (P < 0.001) in these patients. Low CD44 values (cutoff, <200.5 ng/mL) or high CXCL9 values (cutoff, >2.7 ng/mL) at POD 1 differentiated between rejection and no rejection with a sensitivity of 88% or 60% and a specificity of 61% or 79%, respectively. The combination of both biomarker cutoffs at POD 1 had a positive predictive value of 91% and a negative predictive value of 67% for clinically significant ACR. Moreover, CD44 was significantly lower at the time of ACR (P < 0.001) and differentiated the rejection group from patients with graft dysfunction due to other reasons. Our results suggest that CD44 and CXCL9 may serve as predictive biomarkers to identify liver allograft recipients at risk for clinically significant ACR. Liver Transpl 21:1195–1207, 2015. © 2015 AASLD.